2015
DOI: 10.2500/aap.2015.36.3824
|View full text |Cite
|
Sign up to set email alerts
|

Current state of hereditary angioedema management: A patient survey

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
64
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 19 publications
4
64
1
5
Order By: Relevance
“…Thus, we did not expect bias concerning missing responses from respondents. Comparisons of demographics, burden of disease, satisfaction with care, and treatment options between patients with HAE-C1INH and patients with HAE-nlC1INH, as well as between patients with HAE in 2013 3 and 2015, were performed by using 2 tests. A two-sided p value of Ͻ0.05 was considered to be significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we did not expect bias concerning missing responses from respondents. Comparisons of demographics, burden of disease, satisfaction with care, and treatment options between patients with HAE-C1INH and patients with HAE-nlC1INH, as well as between patients with HAE in 2013 3 and 2015, were performed by using 2 tests. A two-sided p value of Ͻ0.05 was considered to be significant.…”
Section: Discussionmentioning
confidence: 99%
“…Among the patients with HAE-C1INH who received prophylaxis, 93% received treatment in their home, either by self or family administration of medication, or via home health care visits; these results were comparable with the 2013 information. 3 More than one-third (39%) reported that they were "very satisfied" with their current prophylactic treatment; 22% were "moderately satisfied," 6% were "mildly satisfied," and 2% reported they were "minimally satisfied" with current prophylaxis (Table 2). Among the patients with HAE-C1INH who received prophylaxis, 20% reported breakthrough attacks at least once per week, 31% reported breakthrough attacks one to three times per month, 15% reported breakthrough attacks once every 2-3 months, and 34% reported breakthrough attacks fewer than once every 6 months (Fig 4).…”
Section: Hae-c1inh ϭ Hereditary Angioedema With C1-inhibitor; Hae-nlcmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Abdominal symptoms of hereditary angioedema typically mimic numerous abdominal emergencies and may delay the correct diagnosis and inappropriate treatments. Ucar et al 28 report on the difficulties experienced by patients with hereditary angioedema in Turkish emergency departments, which is representative of the unmet needs reported globally.…”
mentioning
confidence: 99%
“…24 Using patient surveys, their analysis reveals that despite widespread patient access to on demand and prophylactic treatment options, a significant burden of the disease persists even in treated patients.…”
mentioning
confidence: 99%